2013
DOI: 10.3390/molecules18089195
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Lipopolysaccharide-Induced Proinflammatory Responses by Buddleja officinalis Extract in BV-2 Microglial Cells via Negative Regulation of NF-kB and ERK1/2 Signaling

Abstract: Buddleja officinalis has been traditionally used in the supportive treatment of inflammatory and neuronal diseases in Korea and China. Although several reports have shown the anti-inflammatory effects of Buddleja officinalis, the anti-neuroinflammatory effect has remained unclear. In this study, we aimed to investigate the inhibitory effects of flower buds of B. officinalis Maximowicz water extract (BOWE) on LPS-induced inflammatory processes in BV-2 microglial cells. BOWE dose-dependently inhibited the produc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
27
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(29 citation statements)
references
References 30 publications
2
27
0
Order By: Relevance
“…Although our studies did not include analysis of cPLA 2 , we demonstrated the ability of EGCG from green tea [47] and honokiol, a polyphenol from Magnolia bark, to inhibit NMDA-induced neuronal excitation and ROS production from primary cortical neurons [72]. Study with Buddleja officinalis extract, a traditional Korean herbal medicine used to treat strokes, headaches, vascular diseases and neurological disorders, was shown to exert anti-inflammatory effects (LPS-induced iNOS) by suppressing the ERK1/2 and NF-κB pathways [94]. Wogonin, an active component from the root of the Chinese herbal plant, Huang qin , was shown to attenuate endotoxin/IFNγ-induced PGE2 and NO production in microglial cells through the Src-ERK1/2-NF-κB pathway, albeit the exact involvement of cPLA 2 remains to be further demonstrated [95].…”
Section: Targeting Cpla2 and Upstream Signaling Pathways To Mitigate mentioning
confidence: 99%
“…Although our studies did not include analysis of cPLA 2 , we demonstrated the ability of EGCG from green tea [47] and honokiol, a polyphenol from Magnolia bark, to inhibit NMDA-induced neuronal excitation and ROS production from primary cortical neurons [72]. Study with Buddleja officinalis extract, a traditional Korean herbal medicine used to treat strokes, headaches, vascular diseases and neurological disorders, was shown to exert anti-inflammatory effects (LPS-induced iNOS) by suppressing the ERK1/2 and NF-κB pathways [94]. Wogonin, an active component from the root of the Chinese herbal plant, Huang qin , was shown to attenuate endotoxin/IFNγ-induced PGE2 and NO production in microglial cells through the Src-ERK1/2-NF-κB pathway, albeit the exact involvement of cPLA 2 remains to be further demonstrated [95].…”
Section: Targeting Cpla2 and Upstream Signaling Pathways To Mitigate mentioning
confidence: 99%
“…[2][3][4][5] The recent biological investigations on B. officinalis have been reported that the water extract showed the anti-inflammatory effect via negative regulation of NF-κB and ERK 1/2 signaling in BV-2 cells, 6 and down-regulation of intracellular ROS production and adhesion molecule expression in human umbilical vein endothelial cells, 7 and also exhibited the inhibitory effect on lipid accumulation during 3T3-L1 adipocyte differentiation. 8 Taken together, B. officinalis has been spotlighted by its various phytochemicals and bioactivities.…”
mentioning
confidence: 99%
“…EFBF-AF treatment decreased the nuclear levels of NF-κB p65, relative to those in the LPS only treatment and EFBF-BF-treated samples. Translocation of NF-κB is associated with p-IKK and p-IκB as TLR4 pathway [32]. As shown in Fig.…”
Section: Effects Of Efbf-af On Lps-stimulated Cytokine Expression In mentioning
confidence: 82%